Hepatoprotective effect of leaves of aqueous ethanol extract of Cestrum nocturnum against paracetamol-induced hepatotoxicity (Bangladesh Journal of Pharmacology, 2014)
The hepatoprotective activities of Cestrum nocturnum (Queen of Night) was evaluated against the paracetamol induced hepatotoxicity in the mice. Aqueous ethanol (30:70) extract of plant was obtained by maceration. Results showed that aqueous ethanol extract of C. nocturnum (250 mg/kg and 500 mg/kg) produced significant (p